Bibliotekinės statistikos tobulinimo klausimai - Samėnas, Alvydas (Knygotyra, 1970)
Increasing attention to the questions of library statistics in our country and abroad can be explained by the reason that in the time of great scientific and technical achievements librarianship is uncapable to solve its problems by means of the old methods only. This article deals with some questions which were not definitely solved by the Soviet library statistics. First of all, it mentions that the statistic collections of All-Union character, and those published in the Lithuanian S.S.R. as well, offer insufficient information for statistic analysis of library work. Scientific libraries are given especially little space here. To improve this state of affairs it is necessary to publish more statistic collections with a confined volume of the subjects and cite statistic data about the libraries of all types. For those purposes special periodicals can also be used more widely. In spite of the fact that library methodic centres joined in the right practical usage of the requirements of library statistics, up to this time the units of the stock calculation are not sufficiently clear to the library workers. To guarantee precision of the statistics the author recommends the preparation of directions clearly indicating a nomenclature of the documentation collected by the libraries of all types, and units of calculation. The present state of the terminology of library statistics is not satisfactory either. Statistics need exact determinations of the notions: “reader”. “periodical”, “booklet”, etc. The chief problems of library statistics are to classify the types of libraries and establish the proper system of indices of library work. There are few works in special literature devoted to the study of typological characteristics of every type of library, tendencies of its development, though on the ground of the researches of this kind only, it is possible to create the scientific classification of the types of libraries. For the aims of library statistics all types of the libraries of our country must be devided into two large groups: 1. scientific and special libraries, 2. public libraries or libraries of general education. This group in its turn can be subdivided. This division creates conditions for each group of libraries to search for more exact and efficient indices of its work. The application of the books delivery index is used in the article as an instance to illustrate this statement. The corresponding problems of the international library statistics are also analysed in this article.